Hubungan Kecerdasan Emosional dan Perilaku Orang Tua Terhadap Motivasi Wirausaha Pada Mahasiswa Akhir Unsyiah - Ilhamsyah Fajri; Irin Riamanda; Mirza Mirza; Risana Rachmatan (Fakulatas Dakwah IAIN Salatiga, 2021)
Abstract High entrepreneurial motivation comes from intrinsic and extrinsic. Emotional intelligence is one of the abilities needed to achieve success in all fields, can be a supporter of intrinsic motivation. Parental behavior is a form of extrinsic motivation needed by individuals in career development. Quantitative research method with multivariate correlation type, respondent sample is 263 Unsyiah final students. The sample was selected by simple random sampling technique. Data collection with Motivation to start a business scale, Emotional intelligence scale, Parent career behavior checklist. The results of the study explain that the main hypothesis is accepted, the value of sig is 0.000 0.05, it means that there is a relationship between the independent and dependent variables. The research findings found that emotional intelligence and parental behavior had an effective impact of 18.8% on student entrepreneurial motivation. The results also found that there was no relationship between parental behavior and entrepreneurial motivation. Due to the behavior of parents towards the world of children's careers, it tends to be low, while the motivation of Unsyiah final students tends to be high.AbstrakMotivasi wirausaha yang tinggi berasal dari intrinsik dan eksrinsik. Kecerdasan emosional ialah salah satu kemampuan yang diperlukan guna mencapai kesuksesan di segala bidang, dapat menjadi pendukung motivasi intrinsik. Perilaku orang tua adalah bentuk motivasi ekstrinsik yang dibutuhkan individu dalam pengembangan karir. Metode penelitian kuantitatif dengan jenis korelasi multivariat, sampel responden 263 mahasiswa akhir Unsyiah. Sampel dipilih dengan teknik simple random sampling. Pengumpulan data dengan skala Motivation to start a business, Emotional intelligence scale, Parent career behavior checklist. Hasil penelitian memaparkan hipotesis utama diterima, nilai sig 0,0000,05, bermakna ada hubungan antara variabel independent dengan dependent. Hasil temuan penelitian menemukan kecerdasan emosional dan perilaku orang tua memberikan dampak efektif 18,8% terhadap motivasi wirausaha mahasiswa. Hasil penelitian juga menemukan bahwa tidak adanya hubungan antara perilaku orang tua dengan motivasi wirausaha. Dikarenakan perilaku orang tua terhadap dunia karir anak cenderung rendah, sedangkan motivasi mahasiswa akhir Unsyiah cenderung tinggi.